2019
DOI: 10.3390/w11030517
|View full text |Cite
|
Sign up to set email alerts
|

Flood Resilience of Critical Infrastructure: Approach and Method Applied to Fort Lauderdale, Florida

Abstract: In order to increase the flood resilience of cities (i.e., the ability to cope with flood hazards), it is also crucial to make critical infrastructure functions resilient, since these are essential for urban society. Cities are complex systems with many actors of different disciplines and many interdependent critical infrastructure networks and functions. Common flood risk analysis techniques provide useful information but are not sufficient to obtain a complete overview of the effects of flooding and potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 16 publications
(26 reference statements)
1
47
0
1
Order By: Relevance
“…when the (intangible) connection is within variables and/or human behaviour. Appropriate metrics are essential to objectively measure both direct and indirect impacts; the impact due to a damaging event can be seen as the product of the duration of the event and the overall number of people affected (De Bruijn et al, 2019).…”
Section: Cascading Effects In Cis and Urban Resiliencementioning
confidence: 99%
“…when the (intangible) connection is within variables and/or human behaviour. Appropriate metrics are essential to objectively measure both direct and indirect impacts; the impact due to a damaging event can be seen as the product of the duration of the event and the overall number of people affected (De Bruijn et al, 2019).…”
Section: Cascading Effects In Cis and Urban Resiliencementioning
confidence: 99%
“…The impacts of hurricanes such as Harvey, Irma, Sandy, Florence, and Laura are characteristic examples of hazardous storms that have affected the society and environment of coastal areas and have damaged infrastructure, through the combination of heavy rain and storm surge. The increased frequency of such events raises concerns about compound flood hazards previously considered independent of one another (Barnard et al, 2019;Leonard et al, 2014;Moftakhari et al, 2017;Wahl et al, 2015;Zscheischler et al, 2018;Winsemius et al, 2013;Hallegatte et al, 2013;de Bruijn et al, al., 2017) adds urgency to the need for reassessing CI management policies based on compound impact, to help ensure flood safety and rapid emergency management (Pearson et al, 2018). The uncertainty in the current evolution of compound events translates into an even larger uncertainty concerning future damage to CI (de Bruijn et al, 2019;Marsooli et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the authors assumed that the impact of different flood magnitudes was represented by an increase in the number of substations that failed until the maximum was reached. de Bruijn et al (2019) showed how shared insights among different sectors and stakeholders about critical infrastructure (including power supply) resilience and potential resilience-enhancing measures can be used to quantify resilience.…”
Section: Introductionmentioning
confidence: 99%